La photographie chez Ciaran Carson : imaginaire d’une technique - Catherine Conan (Revue LISA)
This article discusses the importance of the photographic medium in Ciaran Carson’s poetic imagination. Using the concept of the aura developed in Walter Benjamin’s writings on photography, I show that the photographic artefacts featured in Carson’s texts deny their viewers (the poet, and through Carson’s ekphrasis, the reader) a revelation of their intrinsic meaning or value. It is rather photography as a historically developed technology that furnishes Carson’s imagination with a store of poetic images – as opposed to material pictures – borrowed from alchemy and ancient metamorphoses for the pleasure and puzzlement of the reader. Thus the disappearance of the aura from modern photographs that Benjamin mourned is used by Carson as poetic material, or as a pre-text that reestablishes the aura, understood as a genuine encounter between text and reader.